Gingival Crevicular Fluid Levels of Prolidase and Alkaline Phosphatase in Periodontitis - Guven Berrak; Turer Cigdem (Balkan Stomatological Society, 2017)
Background/Aim: The purpose of this study was to investigate gingival crevicular fluid (GCF) alkaline phosphatase (ALP) and prolidase levels in subjects with different periodontal status. Material and Methods: Fifteen periodontitis, fifteen gingivitis and fifteen healthy subject were included. GCF samples were collected from participants. Probing depth, clinical attachment level, gingival index was recorded. ALP and prolidase levels were determined in GCF by spectrophotometrically. Results: Higher values of ALP were found in periodontitis compared with gingivitis and healthy control (p<0.001). The values of prolidase were lower in periodontitis than healthy control (p<0.05). A statistically significant positive correlation was found between clinical parameters and ALP levels (p<0.001). There is no significant correlation between clinical parameters and prolidase levels (p>0.05). Additionally, no significant correlation was detected between ALP and prolidase (r= -0.309, p>0.05). Conclusion: Our preliminary data suggest that low prolidase level in periodontitis was not associated with ALP and clinical parameters, which represent periodontal destruction and inflammation.